2019
DOI: 10.1186/s12889-019-6923-x
|View full text |Cite
|
Sign up to set email alerts
|

A smartphone based attentive eating intervention for energy intake and weight loss: results from a randomised controlled trial

Abstract: Background Laboratory studies suggest that eating more ‘attentively’ (e.g. attending to food being eaten and recalling eating episodes) can reduce food intake among participants with both healthy weight and overweight. The aim of this trial was to assess whether a smartphone application that encourages a more attentive eating style reduces energy intake and promotes weight loss. Methods In an open-label, single centre, parallel groups, individually randomised controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 43 publications
2
32
1
Order By: Relevance
“…Participants also described eating more slowly and stopping eating before finishing their food due to greater awareness of hunger and fullness, most likely due to the attentive eating audio clip that encouraged listeners to eat slowly and pay attention to their hunger and fullness levels. These findings are in contrast to the results of our main trial analyses, which found no effects on trial outcomes at the 8-week assessment, including weight and energy intake in the full sample and among a subsample of participants that were categorized as having used the app as intended [ 20 ]. Our exploratory analyses reported here found that the frequency of recording food consumed was significantly associated with lower body weight at the 8-week assessment but was not significantly associated with body fat percentage.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Participants also described eating more slowly and stopping eating before finishing their food due to greater awareness of hunger and fullness, most likely due to the attentive eating audio clip that encouraged listeners to eat slowly and pay attention to their hunger and fullness levels. These findings are in contrast to the results of our main trial analyses, which found no effects on trial outcomes at the 8-week assessment, including weight and energy intake in the full sample and among a subsample of participants that were categorized as having used the app as intended [ 20 ]. Our exploratory analyses reported here found that the frequency of recording food consumed was significantly associated with lower body weight at the 8-week assessment but was not significantly associated with body fat percentage.…”
Section: Discussioncontrasting
confidence: 99%
“…The trial was prospectively registered on the Open Science Framework [ 21 ] and retrospectively registered at ClinicalTrials.gov (NCT03602001). A full description of the trial design and methods are reported elsewhere [ 20 ]. In brief, this was an 8-week randomized controlled trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of exposure to portion sizes on norm perceptions and expected satiety were potentially stronger (and in the predicted direction) among those participants who were able to correctly identify the portion size to which they were exposed to. This finding may suggest a potential role for making people aware of the portion size as a factor to moderate the relation between portion size exposure and later portion size evaluations, although recent research has failed to demonstrate that training attentive or mindful eating successfully reduces intake [33,34].…”
Section: Discussionmentioning
confidence: 97%
“…Within these studies, there is also mixed evidence as to whether or not attentive eating manipulations enhances memory of eating (Higgs & Spetter, 2018). Additionally, more recent studies with attentive or mindful eating interventions have not reduced future snacking (Tapper & Seguias, 2020;Whitelock, Gaglione, Davies-Owen, & Robinson, 2019;Whitelock, Higgs, Brunstrom, Halford, & Robinson, 2018;Whitelock, Kersbergen, et al, 2019). Further research is needed to clarify the existence of this effect.…”
Section: Memory's Effect On Eatingmentioning
confidence: 98%